Momotaro, the Peach Boy : a traditional Japanese tale - Shute, Linda; Juvenile Collection (Library of Congress) (New York : Lothrop, Lee & Shepard Books, 1986)
Found floating on the river inside a peach by an old couple, Momotaro grows up and fights the terrible demons who have terrorized the village for years.
In standard binding. Issued also in library binding.
Keywords: Folklore -- Japan; Imprints 20th century 1986